Diversity Analysis of Bacterial and Function Prediction in Hurunge From Mongolia - Bao, Wuyundalai; He, Yuxing; Liu, Wei (Frontiers in Nutrition, 2022)
Koumiss is widely concerned by consumers and dairy industry because of its rich nutritional value, many healths benefits and very close to human milk, but the preservation of hurunge is very important for every herdsman who produces koumiss by traditional fermentation. It is very important to successfully produce high-quality koumiss in the coming year. Therefore, in this study, 12 precious samples of hurunge collected from central province of Mongolia: Bulgan Province, Ovorkhangay Province, Arkhangay Province and Tov Province were sequenced based on the V3-V4 region of 16S rRNA gene, and the bacterial diversity and function were predicted and analyzed. There were significant differences in bacterial species and abundance in different regions and traditional fermentation methods(p<0.05). Compared with traditional fermentation methods, the OTUs level of “hurunge” fermented in skin sac was lower, the Acetobacter content was high and the bacterial diversity was different. Firmicutes and Lactobacillus were the dominant bacteria and genera in 12 samples, and the sample QHA contained Komagataeibacter with potential ability to produce bacterial nanocellulose. Functional prediction analysis showed that metabolism-related genes related to bacterial growth and reproduction played a dominant role in microorganisms. To sum up, in-depth excavation of microbial diversity in traditional fermented hurunge is of great significance for the development and research of beneficial microbial resources in the future.